2015
DOI: 10.1016/j.chemgeo.2015.02.039
|View full text |Cite
|
Sign up to set email alerts
|

Nickel isotope fractionation during tropical weathering of ultramafic rocks

Abstract: International audienceAlthough Ni isotopes have been shown to be significantly fractionated in terrestrial samples, their use in continental environmental studies has not yet been evaluated. The present study focuses on an ultramafic (UM) massif (Barro Alto, Goias, Brazil) because such areas are naturally rich in Ni. We present developed lateritic weathering profiles. The goal of the study is to evaluate the potential of using Ni isotopes in environmental continental studies by combining its isotopic signature… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

15
72
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 89 publications
(88 citation statements)
references
References 66 publications
15
72
1
Order By: Relevance
“…Δ 60 Ni soil-rock for A horizon is -0.22 ‰. This trend is previously reported in Albania (Δ 60 Ni soil-rock is up to -0.63 ‰) and at Barro Alto (Estrade et al 2015;Ratié et al 2015). The Ni isotope composition of phytoavailable fraction estimated using the DTPA-CaCl 2 solution shows that heavier Ni isotope pool is released during weathering of ultramafic rocks.…”
supporting
confidence: 64%
See 3 more Smart Citations
“…Δ 60 Ni soil-rock for A horizon is -0.22 ‰. This trend is previously reported in Albania (Δ 60 Ni soil-rock is up to -0.63 ‰) and at Barro Alto (Estrade et al 2015;Ratié et al 2015). The Ni isotope composition of phytoavailable fraction estimated using the DTPA-CaCl 2 solution shows that heavier Ni isotope pool is released during weathering of ultramafic rocks.…”
supporting
confidence: 64%
“…4; Gueguen et al 2013;Estrade et al 2015). The slight differences in Ni isotopic composition of parent rocks from various ultramafic massifs can be explained by variabilities of parent magma and degree of serpentinization causing a possible isotopic fractionation (Ratié et al 2015;Estrade et al 2015). In the last studies, Gall et al (2017) have suggested that serpentinization probably does not affect δ 60 Ni.…”
Section: Phytoavailability Of Metals In Soils and Ni Isotopic Fractiomentioning
confidence: 99%
See 2 more Smart Citations
“…Various studies had conducted related to heavy metal comparison in ultramafic host rocks to the laterization product [5,16]. Equal Ni concentration in the selected samples range from 2,380 to 3,050 ppm, Mn from 959 to 1,260 ppm, Cr from 2,040 to 2,910 ppm, and Co >100 ppm.…”
Section: Major Oxidesmentioning
confidence: 99%